An Empirical Study of Sources of Early Stage Start-Up Funding for Innovative Startup Firms: A Study of Five States of India - Chaudhury, Suman Kalyan; Panigrahi, Anupam; Gaur, Mamta (Indian Journal of Finance, 2019)
Over the past few years, startups have been seen as a taste of the season for India. This has resulted into the materialization of a number of home grown new companies across the country. This development of a novel scenario has been due to the major contributions that led to the mega funding ploughed into most of these new companies between 2007 and 2015. This paper represented the growth of startup companies in India, their types, and possible sources of financing with special emphasis on financing these ventures in the country. In this research, we examined the defining stages of development for startups as well as their funding sources at each stage. The objective of this research paper was to investigate whether India made a shift from conventional to the modern methods of financing. Therefore, this research can be helpful in superior understanding about the funding strategies of entrepreneurial ventures. For conducting the research, a total of five states, that is, Odisha, Chhattisgarh, Jharkhand, West Bengal, and Madhya Pradesh were taken into consideration. This paper is primarily based on survey questionnaires, and the chi-square test was adopted to ascertain the results derived from the information gathered from the respondents. The results revealed that there is an urgent need to provide financial literacy to startups and increase awareness on the activities of angel/VC financing through greater involvement with educational/research institutions and incubation centres.